Knee joint loadings are related to tibial torsional alignments in people with radiographic medial knee osteoarthritis - Huang, Chen; Chan, Ping Keung; Chiu, Kwong Yuen; Yan, Chun Hoi; Yeung, Desmond Shun Shing; Lai, Christopher Wai Keung; Fu, Siu Ngor (PloS one, 2021)
Torsional malalignment was detected in subjects with medial knee osteoarthritis (KOA) but few studies have reported the effect of torsional deformity on knee joint loads during walking. Therefore, this study examined the relationships between lower limb torsional alignments and knee joint loads during gait in people with symptomatic medial KOA using cross-sectional study design. Lower limb alignments including tibial torsion, tibiofemoral rotation and varus/valgus alignments in standing were measured by EOS low-dose bi-planar x-ray system in 47 subjects with mild or moderate KOA. The external knee adduction moment (KAM), flexion moment (KFM) and the KAM index which was defined as (KAM/ (KAM+KFM)*100) during walking were analyzed using a motion analysis system so as to estimate the knee loads. Results revealed externaltibial torsion was positively associated with KAM in subjects with moderate KOA (r = 0.59, p = 0.02) but not in subjects with mild KOA. On the contrary, significant association was found between knee varus/valgus alignment and KAM in the mild KOA group (r = 0.58, p<0.001) and a sign of association in the moderate KOA group (r = 0.47, p = 0.08). We concluded tibial torsion and knee varus/valgus mal-alignments would be associated with joint loading in subjects with moderate medial KOA during walking. Radiographic severity might need to be considered when using gait modification as a rehabilitation strategy for this condition.